Communication of Local People about Myths of Merapi Mountain in Disaster Mitigation - Wardyaningrum, Damayanti (UI Scholars Hub, 2019)
Mount Merapi is one of the most active volcanoes in the world and the local community has long believed several myths related to eruptions of Mount Merapi. Concepts used in the research of communication elements are environment, social, process, symbol, and meaning. This study aims to identify communication of the myths developed in local communities regarding Mount Merapi eruption. Regarding the environmental element, the research found that some people believed myths were the interpretation of messages in dreams related to their natural environment. The social elements described social relations between old generation, who believed in myths, and young generation, who did not believe in the myths. From the point of view of the process element, it was found that the myths have been developed since hundred years ago, i.e. from generations to generations. The elements of symbol used to identify some symbols in the sacrifice ritual activity or signs of Merapi eruption. The meaning elements were used to interpret the local community’s activities and beliefs which contained myths on the eruptions. The messages about the myths were conveyed through informal communication and traditional arts. This study recommends that the belief in myths as traditional knowledge can be integrated with modern knowledge for disaster mitigation.